Creativity, innovation and entrepreneurship in academic training with project-based learning integrated with STEAM - Gazoti, Lilian Amatucci (2024)
This article presents PBL (Project-Based Learning) integrated with STEAM (Science, Technology, Engineering, Arts, Mathematics) and its contributions to academic training, identifying points of consonance regarding creative development, innovation and stimulation of entrepreneurial behavior in vocational technical education. The article will point out the technological trends for the beginning of the 21st century and their relationship with education, and how PBL with a STEAM approach integrates into this scenario, in order to stimulate creativity, innovation and the promotion of entrepreneurship in education. To this end, the research question is how to stimulate creativity, innovation and entrepreneurial behavior through the PBL method integrated with STEAM, in vocational technical education. The methodology adopted was based on the bibliographic review on the PBL method, STEAM and its relationship with technological trends, pedagogical practices in education and entrepreneurship.